Howard Thurman's Mystical Logic: Creatively Encountering Oneness - A Logical Analysis of Thurman's Theology - Neal, Anthony Sean (Black theology, 2017)
Howard Thurman is described on his book covers, which were published during his lifetime, as a poet, mystic, philosopher, and theologian. Aside from this description, locating Thurman among other philosophers and theologians has been difficult owing to the description of his work as non-systematic. In this paper, I argue that (i) Howard Thurman can be located, historically, among other philosophical theologians in general and more specifically as a precursor to Black Theology because of his allowance for his experience to inform him. Then (ii), I also assert that he was systematic in his approach to philosophy and that such an approach was through a mystic framework, which is described in detail here, for the first time.